Analisis Bibliometrik Kecurangan Laporan Keuangan berbasis Vosviewer - Nisa, Tamara; Oktavia, Reni (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This study analyzes the development of research on financial statement fraud using bibliometric methods assisted by VOSviewer. Financial statements present a company's financial information for a given period and are crucial for decision-making by investors, creditors, and stakeholders. The potential for financial statement fraud arises when management seeks to portray an optimal financial condition, often resulting in significant losses for various parties. Utilizing metadata from articles published between 2012 and 2023 obtained through Harzing’s Publish or Perish on Google Scholar, this bibliometric analysis reveals trends, citation patterns, and thematic clusters in the study of financial fraud. The findings indicate a growing interest in this area, with key themes identified such as fraud detection and the relevance of local contexts. This research provides a foundational understanding for future studies on financial statement fraud.